ANALISIS PENGGUNAAN MODEL PEMBELAJARAN HYPOTHETICAL – DEDUCTIVE LEARNING CYCLES UNTUK MENINGKATKAN HASIL BELAJAR IPA-BIOLOGI SISWA SMP - Lopulalan, Silvia E; Watuguly, Theopilus W; Liline, Sintje (Program Studi Pendidikan Biologi FKIP Unpatti, 2022)
Background: Student learning outcomes of SMP Negeri 22 Ambon on the subject of additive biology learning have not yet fully reached the KKM because the learning process only prioritizes the completeness of the material and the learning strategies applied by the teacher still tend to use the lecture method. The Hypothetical-Deductive Learning Cycles (HDLC) learning model provides opportunities for students to construct their own knowledge and act like scientists. This study aims to determine the improvement of science-biology learning outcomes for junior high school students using the hypothetical-deductive learning cycles model of additive material in class VIII SMP Negeri 22 Ambon. Methods: The type of research used is descriptive research which is used to determine the improvement of student learning outcomes. Results: The results of the study illustrate that the learning outcomes of Biology Sciences for junior high school students before the application of the hypothetical - deductive learning cycles learning model were under the KKM, but after the application of the hypothetical - deductive learning cycles model, the SMP students' learning outcomes of Biology turned out to be increased and fulfilled the KKM. Conclusion: Based on the results of research and discussions that have been carried out, it can be concluded that the final score (NA) obtained by each student shows that using the hypothetical-deductive learning cycles model can help students improve learning outcomes.